Capability’ development through ICT enabled business opportunity development model of e-Choupal - Madan, Pankaj; Sharma, Vinay; Seth, Piyush (Journal of Business Economics and Management, 2016)
The purpose of this study is to check how ICT led business opportunity devel- opment model of ITC e-Choupal affected “Capability” development of the people in rural India. The survey of three different regions of India, included 319 e-Choupal beneficiaries and 10 ITC officials and elected representatives of villages. Statistical analysis revealed that Capability Enhancement of farmers depended on the extent to which farmers trusted and participated in ICT activities that varied based on their education level but specifically e-Choupal could generate only limited business opportunities for rural masses. However, the business opportunities definitely affected the capability enhancement parameters. The ICT enabled business models can be well used by corporates and governments of devel- oping economies in Asia and Africa for capability development of rural masses as these models provide new business opportunities for them. The field survey based framework showed how ICT based business opportunity development model of e-Choupal can affect the income, time and saving of farmers in developing economy.